2013
DOI: 10.1007/s00167-013-2372-8
|View full text |Cite
|
Sign up to set email alerts
|

Increased patellofemoral pressure after TKA: an in vitro study

Abstract: Despite correct implantation of the patellar implants and largely unchanged patellofemoral offset, a highly significant increase in pressure after patellar resurfacing was measured. Therefore, from a biomechanical point of view, the preservation of the native patella seems reasonable if there is no higher grade patellar cartilage damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
48
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 44 publications
5
48
0
Order By: Relevance
“…While several authors quantified changes in retropatellar pressures in vitro (16)(17)(18)(19), to the authors' knowledge, there are no published studies that demonstrated whether such forces and pressures have any relation to pain or function. Patellar morphology is known to influence patellofemoral pressure (18,20,22), congruence (23,24) or instability (23,25), and while it is often associated with tilt (23,24), it does not necessarily correlate with poor outcomes (22,25).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While several authors quantified changes in retropatellar pressures in vitro (16)(17)(18)(19), to the authors' knowledge, there are no published studies that demonstrated whether such forces and pressures have any relation to pain or function. Patellar morphology is known to influence patellofemoral pressure (18,20,22), congruence (23,24) or instability (23,25), and while it is often associated with tilt (23,24), it does not necessarily correlate with poor outcomes (22,25).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous authors observed that TKA increases patellofemoral pressures, particularly in mid-and late flexion (16)(17)(18)(19). Recent in vitro studies demonstrated that retro-patellar pressures are influenced by trochlear geometry, as well as the morphology of the native patella, or the shape of the patellar button (16)(17)(18)20).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The data were in contrast to the biomechanical findings reported by others. It has been shown that patellofemoral pressure increases up to 1.5-2.5 times after TKA in comparison with the natural knee [13]. Studies have also reported about the impact of the component design on femoropatella pressure [4].…”
mentioning
confidence: 99%